THE ANALYSIS OF FACTORS THAT INFLUENCE COMMUNITY'S INTEREST IN MONEY WAKAF IN BOGOR DISTRICT: MUSLIM SOCIETY PERSPECTIVE - Septiani, Ane Tri; Fauzi, Achmad; Mardi; Respati, Dwi Kismayanti (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of Understanding, Income, Religiosity, and Access to Information on Interest in Cash Waqf in Bogor Regency. The data collection method used is a survey method with a correlational approach. The affordable population in this study is the Muslim community of productive age in Bogor Regency, amounting to 3,261,138 people. Data was obtained by distributing a questionnaire with a sample of 350 people with the determination using the formula ISAAC table and MICHAEL and using the proportional sampling technique. The novelty in this study is the object of Research and perspectives which have not been found in previous studies. The data analysis technique used is multiple regression analysis, analysis prerequisite test, and hypothesis testing. The results showed that Understanding had a positive effect on the interest in cash waqf. Income has a positive impact on interest in cash waqf. Religiosity has a positive impact on the interest in cash waqf. And Information Access has a positive effect on the good in cash waqf.